A study of salt weathering cycles impact on limestones - Alves, C. (2017)
Here are discussed results of salt weathering laboratory tests on specimens of three limestones, two grainstones (designated as Semi-rijo and Moca Creme) and a travertine, considering parameters related to an initial ma ss in creasing phase and to mass differences between cycles in the mass decreasing phase. Results show a good ordinal correlation between final mass loss and maximum difference between cycles that differentiates the considered rock types.